Discovery of potent and noncovalent KRASG12D inhibitors: Structure-based virtual screening and biological evaluation - Wang, Yuting; Zhang, Hai; Li, Jindong; Niu, Miao-Miao; Zhou, Yang; Qu, Yuanqian (Frontiers in Pharmacology, 2022)
KRASG12D, the most common oncogenic KRAS mutation, is a promising target for the treatment of pancreatic cancer. Herein, we identified four potent and noncovalent KRASG12D inhibitors (hits 1-4) by using structure-based virtual screening and biological evaluation. The in vitro assays indicated that the four compounds had sub-nanomolar affinities for KRASG12D and showed a dose-dependent inhibitory effect on human pancreatic cancer cells. In particular, the hit compound 3 was the most promising candidate and significantly inhibited the tumor growth of pancreatic cancer in tumor-bearing mice. The hit compound 3 represented a promising starting point for structural optimization in hit-to-lead development. This study shows that hit compound 3 provides a basis for the development of the treatment of cancer driven by KRASG12D.